Analysis of variation of water quality parameters along treatment processes in OPA waterworks, ILE-IFE, Nigeria - O. Jeje, J.; O. Fadipe, O.; T. Oladepo, K. (International Journal of Physical Research, 2022)
This study was conducted to assess the variation of water quality parameters along the treatment processes of Opa Waterworks at Obafemi Awolowo University, Ile – Ife, Nigeria. This was to ascertain how chemical and physical parameters vary along the treatment plant visits while at the same time ensuring that the influent and effluent conforms to water quality standards set by the World Health Organization.Determination of physicochemical parameters; pH, temperature, conductivity, turbidity, nitrate and chloride was done by  using standard methods while a colorimetric,  and atomic absorption spectrometry methods were used for the selected heavy metals; cadmium, zinc and copper.It was observed that for the influent, the concentration of lead was 9.44 mg/l, nitrate 0.25 mg/l, chloride 18.27 mg/l, sulphate 4.29 mg/l, copper 4.55 mg/l, zinc 0.07 mg/l and cadmium 1.10 mg/l. For the effluent, the concentration of nitrate was 0.22 mg/l, chloride 16.01 mg/l and sulphate 4.29 mg/l while that of lead, copper, zinc and cadmium was 0.00 mg/l. The overall results show that the concentrations of the water quality parameters tested conform to the World Health Organization water quality standards at the effluent points of the treatment plant.